Cold Spraying as a Repair Method for Crankshaft Journals - Blomgren , Matilda; Gunnarsson, Stefán (My University, 2023)
In this study, the feasibility of repairing crankshaft journals with cold spraying was investigated. It was researched through a systematic literature study, and contact with cold spraying companies, with the main focus on the parameters affecting the coating properties; surface hardness and adhesive strength, machinability of the cold sprayed coating, and limitations to the shape and size of repair. The most critical factor affecting the deposit hardness and adhesive strength is the impact velocity. The size and shape of the repair are limited by both the cold spraying process capacity and the crankshaft design. The design elements limiting shape and size are the critical zones; radiuses, oil holes, and the lower part of the pin journals. Machining the cold sprayed coating is possible, however, it can be problematic due to the critical zones and simultaneous machining of two materials. The cold spraying companies, which differ by the pressure system they specialize in, have recommended materials for the repair, only the recommendation from the high pressure cold spraying company can fully meet the design requirements. For low-pressure cold spraying, three feedstock materials have been recommended, Ni/Zn, Al/Zn, and Cu/Zn composites. For high-pressure cold spraying, two feedstock materials have been recommended, a tungsten carbide with nickel and cobalt, and a tungsten carbide with stainless steel. The latter can be further developed to meet the crankshaft requirements. The recommended materials must comply with Volvo’s list of substances. The recommended feedstock materials include substances on the lists. The materials shall therefore be assessed if allowed to be used, if not it must be considered if other feedstock materials are available, or if the material open for development can be optimized with the lists in mind. A detailed recommended plan of testing is presented with the purpose of defining the unknown parameters of the coatings; compatibility and strength, and to verify that the coating meets all journal requirements.
Keywords: Cold spray; Crankshaft; Journal; Low-pressure cold spray; High-pressure cold spray